Effectiveness and efficiency of an 11-week exercise intervention for patients with hip or knee osteoarthritis: a protocol for a controlled study in the context of health services research - Inga Krauss; Gerhard Mueller; Georg Haupt; Benjamin Steinhilber; Pia Janssen; Nicola Jentner; Peter Martus (BMC, 2016)
Abstract Background Osteoarthritis is the most common reason for pain in older adults, and the individual and economic burden of this disease is immense. The chronic character of osteoarthritis requires a long-term therapeutic treatment. In this regard life-style interventions such as physical exercises that can be carried out by the patient himself are recommended as first line treatment. There is evidence for the short-term benefit of exercise therapy in terms of pain reduction and physical functioning. Nonetheless research agendas highlight the need for multifaceted interventions that incorporate exercise strategies into patient care. Studies should be conducted with appropriate sample sizes and should allow statements on long-term effects as well as cost-utility and safety. These open questions are under the scope of this study. Methods/design This is a controlled study in the context of health services research. The study population consists of n = 1400 subjects with hip or knee osteoarthritis. The intervention group will be recruited from participants of a country-wide health insurance offer for people with hip or knee osteoarthritis. Potential participants for the control group (ratio 10:1 (control vs. intervention) will be filtered out from the insurance data base according to pre-defined matching criteria and asked by letter for their participation. The final statistical twins from the responders (1:1) will be determined via propensity score matching. The progressive training intervention comprises 8 supervised group sessions, supplemented by home exercises (2/week over 11 weeks). Exercises include mobilization, strengthening and training of postural control. Primary outcomes are pain and function measured with the WOMAC Index immediately after the intervention period. Among other things, health related quality of life, self-efficacy, cost utility and safety will be evaluated as secondary outcomes. Participants will be followed up 6, 12 and 24 month after baseline. Discussion Results of this trial will document the effects of clinical as well as economic outcomes in a regular health care setting on the basis of a large sample size. As such, results of this trial might have great impact on future implementations of group- and home-based exercises in hip or knee osteoarthritis. Trail registration German Clinical Trial Register DRKS00009251 . Registered 10 September 2015.